Modern Strategies for Heterocycle Synthesis - Favi, Gianfranco (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Heterocycles feature widely in natural products, agrochemicals, pharmaceuticals and dyes, and their synthesis is of great interest to synthetic chemists in both academia and industry. The contributions of recent applications of new methodologies in C-H activation, photoredox chemistry, cross-coupling strategies, borrowing hydrogen catalysis, multicomponent and solvent-free reactions, regio- and stereoselective syntheses, as well as other new, attractive approaches for the construction of heterocyclic scaffolds are of great interest. This Special Issue is dedicated to featuring the latest research that is ongoing in the field of heterocyclic synthesis. It is expected that most submissions will focus on five- and six-membered oxygen and nitrogen-containing heterocycles, but structures incorporating other rings/heteroatoms will also be considered. Original research (communications, full papers and reviews) that discusses innovative methodologies for assembling heterocycles with potential application in materials, catalysis and medicine are therefore welcome.